Determinants of Low Birth Weight Among Newborns Delivered in Silte Zone Public Health Facilities, Southern Ethiopia: A Case-Control Study - Seid S; Wondafrash B; Gali N; Ali A; Mohammed B; Kedir S (Dove Medical Press, 2022)
Shafi Seid,1 Beyene Wondafrash,2 Nurzeman Gali,2 Abdulfeta Ali,1 Bekri Mohammed,3 Shemsu Kedir4 1Department of Maternal and Child Health, Silti Woreda Health Office, Kibet, Ethiopia; 2Department of Nutrition and Dietetics, Jimma University, Jimma, Ethiopia; 3Department of Nutrition, University of Gondar, Gondar, Ethiopia; 4Department of Public Health, Werabe University, Werabe, EthiopiaCorrespondence: Shemsu Kedir, Tel +251 932603556, Email shemsukedir6@gmail.comBackground: Low birth weight is a challenging public health problem, which has wide range of both short- and long-term consequences particularly in developing countries. Although several studies have been conducted in different countries including Ethiopia, most of the studies did not consider the food security status, environmental-related and maternal dietary diversity-related factors. Therefore, this study aimed to identify contextual determinant factors of low birth weight.Method: A facility-based unmatched case-control study design was employed among 84 cases and 168 controls in selected public health facilities of the Silte Zone. Cases were newborns with birth weight less than 2500gm and controls were newborns with birth weight greater than 2500gm. The data were collected using a semi-structured, pretested interviewer-administered questionnaire. Multivariable logistic regression analysis was carried out to identify independent determinants of low birth weight with a p-value < 0.05.Results: The mean birth weight was 2154.94gm ± 233.43 gm SD for cases and 3022.92gm ± 311.88 gm for controls. Mothers who did not receive iron and folate supplementation during pregnancy (AOR = 4.17, 95% CI: (1.44, 12.3)), not taking additional meal (AOR = 3.09, 95% CI: (1.28, 7.5)), maternal hemoglobin level < 11g/dl (AOR = 5.213, 95% CI (1.92, 14.13)), household food insecurity (AOR = 6.85, 95% CI: (3.01, 15.61)) and women's inadequate minimum dietary diversity score (AOR = 4.13 (1.4, 12.16)) were found to be independent determinants of low birth weight.Conclusion: Missing of iron and folate supplementation during pregnancy, maternal meal frequency during pregnancy, maternal hemoglobin level, food insecurity, and women's inadequate minimum dietary diversity score were significant determinants of low birth weight. Thus, public health intervention in the field of maternal and child health should be addressed by strengthening multi-sectoral efforts, which improve women's dietary diversity, adherence of iron folate, additional meal and food security.Keywords: low birth weight, preterm, newborn